Unia Europejska wobec Bałkanów Zachodnich w kontekście kryzysu migracyjnego w latach 2015‑2019 (Politeja, 2020)
European Union towards Western Balkans in the Context of Migration Crisis 2015‑2019The aim of the article is to analyse the actions taken by the European Union towards the Western Balkans in the context of the migration crisis. The study assumes that the migration crisis was an important factor accelerating the accession process of the Western Balkan countries to the European Union. In order to fulfil the research goal, an analysis of sources (European Union documents) was conducted. The paper uses elements of the theory of the regional security complex as a theoretical framework. Firstly, the activities of the European Union before the migration crisis are discussed. Next, the paper focuses on presenting the course of the crisis on the Western Balkan route. The further part of the study discusses the actions taken by the EU towards the countries of the Western Balkans in response to the migration crisis.